24 Direct Admission to a Pacing Centre of Patients Who Present Urgently for Pacing: Prospective Pilot Study of Feasibility and Length of Stay. (31st May 2014) - Bates, Matthew; Robinson, Nicola; McComb, Janet
Abstract : Introduction: A retrospective modelling study of patients presenting to the emergency department in our trust, who were then transferred to our hospital and paced urgently, suggested 60% could have been admitted directly to our pacing centre with a potential saving of 3 bed days per patient. Simple triage criteria of initial heart rate (HR) ≤ 50bpm or high-grade atrio-ventricular block (AVB) and the absence of comorbidity requiring specific treatment prior to pacing would have identified >90% of those suitable for direct admission. A prospective pilot study tested the hypothesis that these criteria could be used successfully to select patients for direct referral to the pacing centre, with reduction in length of stay. Methods: All patients undergoing urgent pacing at our centre during 26 weeks in 2013 were included in an observational study. Demographic, clinical and length of stay data were analysed. Results: 35 of the 83 consecutive patients paced during the study period were excluded from analysis: bradycardia occurred following cardiac procedures in 27, and with complex co-morbidities in 8, who were referred as in-patients from older people's medicine. 48 were therefore included in analysis: origin of referral was our local referring hospital (33 patients), or other hospitals (8) following emergency admission, primary care / cardiology outpatients (6), and the ambulance service (1). Mean age was 80 ± 10 years, 63% were male. 24 (50%) fulfilled our direct referral criteria, of whom 19 (79%) were actually referred via this route. Reasons for unsuitability for direct referral were lack of pacing indication at presentation (12), infection or complex comorbidity (8), and trauma (4). HR ≤ 50 bpm or high grade AVB as a single triage criterion would have resulted in identification of 63% and 79% of the 24 suitable patients, respectively. Initial HR was lower (46 ± 16 vs 63 ± 24 bpm, .01) and the pacing indication more frequently AVB (89% vs 48%, .01) in those directly referred compared to those routinely referred; all other clinical parameters were similar. Of the patients suitable for direct referral, time from admission to pacing was significantly reduced in those that were directly referred, compared to those that were not (0.6 ± 0.7 vs 4.4 ± 3.2 days, p < 0.01). Conclusions: Using simple triage criteria, direct referral to a pacing centre is possible in 50% of an elderly population presenting urgently for pacing, and results in a saving of nearly 4 bed days for each patient directly referred.